PENGGUNAAN BAHASA JERMAN DALAM BIDANG PARIWISATA (DEUTSCH FÜR TOURISMUS) - Surya Masniari Hutagalung (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
This article describes the use of German in Tourism. The purpose of this presentation is as a follow up to a small part of the results of the tracer study conducted for the development of the Deutsch für Tourismus course, under the research